Empowering citizens in the context of deliberation processes - Wrona, Aleksandra (Wzmacnianie pozycji obywateli w kontekście procesów deliberacyjnych, 2021)
Different processes in creating policies of development can be observed, some of which need to be supported. One of the most important issues of new policies is empowering citizens provided by various methods. The research is based on literature studies that show how broad this subject is. Other methods include statistical analyses which made it possible to perceive a correlation between different factors and a benchmark based on the example of the deliberation process in a project prepared by NGOs and the municipality of Warsaw. The aim of the research was to describe the relations and connections between empowering citizens, the deliberation processes and building trust in the local authorities. An interesting outcome of the research was creating a recommendation for policy makers based on the observation that building a dialogue between local governance and citizens can be significant for future sustainable development.
Biblioteka Regionalisty, 2021, Nr 21, s. 136-147
Keywords: empowering citizens; deliberation processes; decision-making; urban policies; social participation; wzmacnianie pozycji obywateli; procesy deliberacyjne; procesy decyzyjne; polityki miejskie; partycypacja społeczna